AIRIS Smart Inhaler: An Integrated Health Technology Innovation to Improve Early Detection and Proactive Control of Asthma Attacks - Fanny Afnan Jannati; Siti Syarah Yuliska; Syaikhah Zhafirah Sitorus; Afryansyah Afryansyah (Universitas Islam Negeri Sumatera Utara, 2025)
Asthma is a chronic respiratory disease of the airways characterized by inflammation narrowing of the airways, causing sufferers to experience difficulty breathing. This disease requires long-term management and consistent monitoring of medication use. However, the use of inhalers as asthma therapy is not regularly used due to low awareness and minimal monitoring. This has led to a surge in asthma relapse cases. Therefore, a solution is needed to help increase awareness and monitor inhaler use in real-time, while supporting patient adherence to treatment. The research method used is a Research and Development (R&D) approach, involving prototype design, functional testing, and initial system evaluation. This device is designed to track inhaler usage patterns, detect potential symptoms through manual input and environmental data, and provide real-time notifications via a companion app. Testing results show that the AIRIS Smart Inhaler can automatically detect inhaler usage, record frequency and usage time, and send this data to the companion app in real-time. This system also successfully provides usage reminders to users. With this feature, AIRIS is considered to be able to improve therapy compliance and facilitate monitoring by medical personnel. AIRIS Smart Inhaler is expected to improve therapy compliance, facilitate asthma monitoring, and become an innovative solution in technology-based asthma management.